2013
DOI: 10.1016/j.jtcvs.2012.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of poststernotomy wound infections in obese patients by negative pressure wound therapy

Abstract: Negative pressure wound dressing treatment over clean, closed incisions for the first 6 to 7 postoperative days significantly reduces the incidence of wound infection after median sternotomy in a high-risk group of obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
120
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 19 publications
2
120
0
4
Order By: Relevance
“…After removal of duplicates, 872 remained. Eighty‐three full‐text papers were retrieved for inspection, of which seven were RCTs33, 34, 35, 36, 37, 38, 39. A further six unpublished studies were identified through contact with manufacturers and by searching ClinicalTrials.gov.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After removal of duplicates, 872 remained. Eighty‐three full‐text papers were retrieved for inspection, of which seven were RCTs33, 34, 35, 36, 37, 38, 39. A further six unpublished studies were identified through contact with manufacturers and by searching ClinicalTrials.gov.…”
Section: Resultsmentioning
confidence: 99%
“…(personal communication), used an NPWT device (VAC®) and six34, 35, 38, 39, including those of S. Karlakki et al . and R. Galiano et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations